Hitler and Nazi Germany - Lee, Stephen J., 1945- (London ; New York : Routledge, 1998)
'Hitler and Nazi Germany' examines the major themes of Hitler's rise to power and Nazi domestic and foreign policies through to the end of World War II. Combining narrative, the views of different historians and a selection of sources, this book provides a concise introduction and study aid for students. -- publisher
1. The rise of Nazism -- 2. The establishment of dictatorship -- 3. Indoctrination, propaganda and terror -- 4. Support and opposition -- 5. The Nazi economy -- 6. Race, the Holocaust and the Jewish response -- 7. Foreign policy and war.
Includes bibliographical references (p. 118-119) and index.
The Roger Griffin ComFas Collection
Keywords: Hitler, Adolf, -- 1889-1945.; National socialism; Holocaust, Jewish (1939-1945); Racism -- Germany; Germany -- Politics and government -- 1933-1945.